2021
DOI: 10.3390/ijerph182413031
|View full text |Cite
|
Sign up to set email alerts
|

Spatio–Temporal Heterogeneity of Urban Expansion and Population Growth in China

Abstract: Urbanization has become one of the hot issues of global sustainable development, and is mainly characterized by urban population growth and construction land expansion. However, the inharmonious development of urban expansion and population migration has brought serious challenges to urban planning and management. China is the largest developing country in the world, and the urbanization process has accelerated over the past decades. In this paper, decoupling analysis was used to demonstrate the spatio–tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…It is no doubt that the risk of lung cancer death will increase once the elderly population becomes more vulnerable to lung cancer risk factors (air pollution or tobacco exposure, etc.) ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is no doubt that the risk of lung cancer death will increase once the elderly population becomes more vulnerable to lung cancer risk factors (air pollution or tobacco exposure, etc.) ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies therefore need to build models in this theoretical framework, which corroborates existing studies that have found different effects of urbanization development-related indicators on haze pollution in different cities, regions and stages. Finally, the urbanization in mainland China is characterized by a lag in population urbanization and a lack of coordination between the two, which has led to many problems in the economic development of mainland China (Liu et al, 2021b), and therefore the impact of the lack of coordination between population urbanization and land urbanization on haze pollution needs to be discussed, which has not been analyzed in depth in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The inconsistency between population urbanization and land urbanization is essentially the unreasonable structure and allocation of factors (Lei et al, 2022). And in China, this inconsistency is particularly evident in the rapid urbanization of the land (Liu et al, 2021b), that land are over-allocated to cities and labour become relatively scarce. This distorted allocation of factors has led to extensive land use, which is useless for economic efficiency and environmental protection.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…These changes have become an elemental driving force for social development, generating substantial spatiotemporal changes (Liang et al, 2021 ; Chen, 2010a ; Qu et al, 2019 ; Long et al, 2010 ; Yu et al, 2007 ). Meanwhile, owing to the high uniformity of urban and rural development within Chinese prefecture-level cities, a prefecture-level city is often considered a regional complex that integrates urban and rural areas (Liu et al, 2021 ; Liu et al, 2020 ; Li et al, 2020 ; Tu and Long, 2017 ; Zhao, 2013 ). Spatial correlations in domestic prefecture-level cities drives similarities and differences in the urban–rural integral landscape among prefecture-level cities.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the COVID-19 pandemic (since the early 2010s), China’s economy had been in a state of rapid growth. Specifically, the development of leading industries, primary industries, and the bubble economy played a significant role in facilitating the rapid development (Liu et al, 2021 ; Duan et al, 2017 ; Wu et al, 2014 ). In the early 2010s, the development of Chinese prefecture-level cities was generally evolutionary; it was both ordered and chaotic.…”
Section: Introductionmentioning
confidence: 99%